2007
DOI: 10.1080/01612840701252956
|View full text |Cite
|
Sign up to set email alerts
|

Creativity in Older Adults: A Plethora of Possibilities

Abstract: Aging continues to be an important topic of study. For many older adults, the elder years can be a challenging, if not difficult, time. Creativity interventions have been shown to positively affect mental and physiological health indicators. The process of creating and one's attitude toward life may be more important than the actual product or tangible outcome. While many activities are those typically thought of as creative, such as painting, there are also a number of useful interventions that are not tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 27 publications
4
62
0
7
Order By: Relevance
“…This experience enhanced respondents' view of self, which also affirms Sarvimäki and Stenbock-Hult Lie's (2000) claim that effort and application in the face of restrictions may lead to the strengthening of self-worth, because of the sense of control combined with the feeling of pride in what can be achieved. Likewise, Fisher and Specht (1999), as cited by Flood and Phillips (2007), aver that older adults engaging in creative activities are strengthening their sense of self that is competent, efficacious, and capable of doing. traditional Filipino art, a form of recreational therapy empowers the elderly by revealing their inherent abilities and uniqueness as persons, honoring life experience and gained wisdom (Stephenson, 2006).…”
Section: Making It Happenmentioning
confidence: 93%
See 2 more Smart Citations
“…This experience enhanced respondents' view of self, which also affirms Sarvimäki and Stenbock-Hult Lie's (2000) claim that effort and application in the face of restrictions may lead to the strengthening of self-worth, because of the sense of control combined with the feeling of pride in what can be achieved. Likewise, Fisher and Specht (1999), as cited by Flood and Phillips (2007), aver that older adults engaging in creative activities are strengthening their sense of self that is competent, efficacious, and capable of doing. traditional Filipino art, a form of recreational therapy empowers the elderly by revealing their inherent abilities and uniqueness as persons, honoring life experience and gained wisdom (Stephenson, 2006).…”
Section: Making It Happenmentioning
confidence: 93%
“…Aging not only brings about physical change, but also a decline in capabilities along with financial restrictions and role deterioration (Flood & Phillips, 2007) in the family and community, which may bring about depression. Findings of this study provide significant and insightful information regarding the overall state of a select group of Filipino older individuals housed in an institutionalized care setting.…”
Section: Me Myself and Melancholymentioning
confidence: 98%
See 1 more Smart Citation
“…Most creativity training programs work, especially when divergent thinking -the capacity to generate multiple alternative solutions as opposed to one correct solution -is fostered (Scott et al 2004 ) . Many interventions help to increase creativity in older adults, such as cultural/art programs (e.g., music, dance, drawing), poetry, journaling, problem-solving activities, reminiscence, and psychoeducational groups (Flood and Phillips 2007 ) .…”
Section: Wisdom Strengthsmentioning
confidence: 99%
“…Research has identified the benefits when older adults took part in RT [21,22]. Creative activities nurture the sense of competence and capabilities, which assist older adults to adjust to the physically, psychologically or psychosocially changes around them.…”
Section: Introductionmentioning
confidence: 99%